Amit Jain’s new ‘rule of 3’ for diabetic foot: an excellent compilation - S. J., Haridarshan (International Surgery Journal, 2018)
We have seen over last decade various new concepts in the field of diabetic foot. Most of them aimed at simplifying the concepts in diabetic foot. The latest concept being the Amit Jain’s system of practice, a modern diabetic foot surgical approach, that was designed and created by Amit Jain, one of the pioneering Diabetic foot surgeon. This is the first new principle and practice in diabetic foot being proposed from Indian subcontinent that aimed at improvising and standardizing diabetic foot globally. Amit Jain’s rule of 3 is the new concept which is an excellent compilation of all the 3’s that can be seen in diabetic foot. This article throws a brief highlight on this new innovative rule.